Briquetting of Cassava Peel (Manihot Esculenta) With Styrofoam Adhesive as Alternative Fuel - Afif Thaifuri; Nurmahni Harahap (Winaya Inspirasi Nusantara Foundation, 2024)
Briquetting technology that uses cassava peels as a base material has the potential to reduce dependence on conventional fuels and maintain environmental sustainability. Cassava peel waste can be used as an alternative solid fuel source. The aim of this research is to explore the process of making briquettes from cassava peels with added styrofoam adhesive, which can be used as an alternative to petroleum and natural gas. The research involved five stages, namely preparation, drying, mixing, burning, and quality testing. The method used was experimentation by testing cassava peel briquettes against the parameters of briquette mass, combustibility, and water heating time. The results showed that the average mass of briquettes after the production process was about 0.16 kg. The fastest burning time is 67 minutes 02 seconds, and the fastest 100 mL water heating time is 1 minute 05 seconds.